Interventions to reduce preterm birth in pregnant women with psychosocial vulnerability factors–A systematic review. (September 2021) - Pedersen, Johanne Frøsig; Kallesøe, Sarah Boutrup; Langergaard, Sofie; Overgaard, Charlotte
Highlights: Pregnant women with psychosocial vulnerability face a higher risk of preterm birth. Understanding the complexity of psychosocial vulnerability may improve antenatal care. Antenatal group meetings initiated in second trimester had the greatest effect. Group meetings facilitated by the same midwife had the greatest likelihood of effect. Abstract: Objective: Pregnant women with psychosocial vulnerability factors face a higher risk of preterm birth, a heavier burden of perinatal morbidity and mortality and less social health equity. Prevention of preterm birth in this group has proved difficult, and more knowledge is needed to ensure evidence-based care and improve prevention. This study aimed to determine the effectiveness of preventive interventions to reduce preterm birth among pregnant women with psychosocial vulnerability factors. Design: A systematic review of preventive interventions was conducted, searching the databases Cinahl, Cochrane Library, Embase, ProQuest, PsycInfo, PubMed and Scopus to identify RCT's. The search was completed on October 14, 2019. Using the Cochrane Collaboration tools, quality assessments were made, and independent single-data extraction was conducted. Due to heterogeneity in, e.g., participant characteristics, intervention content and duration, the data were synthesised qualitatively. Included studies were ranked in evidence-based hierarchical order, elucidating the risk of bias of each individual study, all of which were ranked as having a medium or low level of evidence. Findings: We identified 1, 562 articles, of which five focused on prevention of preterm birth, met our predefined criteria for inclusion and quality assessment, and were therefore included. Interventions consisted of home visits in two studies, group meetings in one study, phone calls in one study, and physical massage in the last study. Four transverse themes arose: intervention intensity, initiation, continuity of care, and the healthcare professionals' educational background. Key conclusions: The evidence base for interventions aiming to prevent preterm birth among pregnant women with psychosocial vulnerabilities is limited. Interventions based on ten antenatal group meetings initiated during the second trimester and facilitated by the same midwife have the greatest likelihood of being effective. Continuity in intervention delivery and healthcare professional's educational background may positively impact the efficiency of the intervention. Further research is needed to address questions about the impact of intervention initiation and intensity and its degree of continuity and mode of delivery.